Plant community diversity will decline more than increase under climatic warming. (27th January 2020) - Harrison, Susan
Abstract : Regions and localities may lose many species to extinction under rapid climate change and may gain other species that colonize from nearby warmer environments. Here, it is argued that warming-induced species losses will generally exceed gains and there will be more net declines than net increases in plant community richness. Declines in richness are especially likely in water-limited climates where intensifying aridity will increasingly exceed plant tolerances, but also in colder temperature-limited climates where steep climatic gradients are lacking, and therefore, large pools of appropriate species are not immediately adjacent. The selectivity of warming-induced losses may lead to declines in functional and phylogenetic diversity as well as in species richness, especially in water-limited climates. Our current understanding of climate-caused diversity trends may be overly influenced by numerous studies coming from north-temperate alpine mountaintops, where conditions are unusually favourable for increases—possibly temporary—in local species richness. This article is part of the theme issue 'Climate change and ecosystems: threats, opportunities and solutions'.